World health system performance revisited: the impact of varying the relative importance of health system goals - Murray Christopher JL; Lovell CA Knox; Lauer Jeremy A; Evans David B (BMC, 2004)
Abstract Background In 2002, the World Health Organization published a health system performance ranking for 191 member countries. The ranking was based on five indicators, with fixed weights common to all countries. Methods We investigate the feasibility and desirability of using mathematical programming techniques that allow weights to vary across countries to reflect their varying circumstances and objectives. Results By global distributional measures, scores and ranks are found to be not very sensitive to changes in weights, although differences can be large for individual countries. Conclusions Building the flexibility of variable weights into calculation of the performance index is a useful way to respond to the debates and criticisms appearing since publication of the ranking.